2023
DOI: 10.1002/cmdc.202300018
|View full text |Cite
|
Sign up to set email alerts
|

Double BAC and Triple BAC: A Systematic Analysis of the Disinfectant Properties of Multicationic Derivatives of Benzalkonium Chloride (BAC)

Abstract: Over the past decades, the shortcomings of established quaternary ammonium disinfectants have become increasingly clear. Although benzalkonium chloride (BAC) has enjoyed nearly a century of significantly protecting human health through surgical preparation, home use, and industrial applications, increasing levels of bacterial resistance have rendered it decreasingly effective. In light of more recent efforts that have informed us that multicationic amphiphilic disinfectants show both higher activity as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Recent research investigations have demonstrated that in contrast to quaternary ammonium salts such as benzalkonium chloride (BAC), which have been used for decades, multicationic disinfectants are more effective and rarely lead to the development of resistance by various types of microorganisms [150,151]. The weaknesses of traditional quaternary ammonium disinfectants have become more apparent in the last few decades, so many research teams are working on the development of novel and more effective MHCS structures.…”
Section: Biocidal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research investigations have demonstrated that in contrast to quaternary ammonium salts such as benzalkonium chloride (BAC), which have been used for decades, multicationic disinfectants are more effective and rarely lead to the development of resistance by various types of microorganisms [150,151]. The weaknesses of traditional quaternary ammonium disinfectants have become more apparent in the last few decades, so many research teams are working on the development of novel and more effective MHCS structures.…”
Section: Biocidal Agentsmentioning
confidence: 99%
“…The multi-cationic homologs of benzalkonium chloride (BAC) are one of the structures that research teams are now working on, and they look the most promising. In the paper published by Toles et al [150], the researchers successfully obtained triscation BAC analogues (Tris-BAC) and showed that their antimicrobial activity was significantly greater than that of monocationic BAC. In this study, the authors demonstrated that multicationic derivatives of BAC had biological activity against the Gram-positive and Gram-negative bacteria in the single-digit micromolar range.…”
Section: Biocidal Agentsmentioning
confidence: 99%
“…BKC is water-soluble and widely used as an antibacterial agent, antiseptic, and preservative. [12][13][14] BKC has agricultural, industrial, and clinical applications. However, concerns about the safety of BKC, especially its mutagenicity and the bacterial resistance to BKC, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, benzalkonium chloride (BKC) was the target pharmaceutical to be removed. BKC is water‐soluble and widely used as an antibacterial agent, antiseptic, and preservative 12–14 . BKC has agricultural, industrial, and clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The tris-QACs (especially with a pyridine core and three alkyl tails) as biocides have been studied very little. Currently, there are only a few works covering this subject [ 20 , 21 , 22 , 23 , 24 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%